Pancasila Sebagai Fondasi Moral Dan Intelktual Bangsa Realitas Dan Tantangan Dalam Konteks Masyarakat Modern - Pratama, Ardine Hardiyanto; Putranami, Muammad Fachri; Giovany, Daffa Farrel (Eastasouth Institute, 2024)
Pancasila as the Indonesian state philosophy has an important role in guiding individual behavior and social order. However, in the modern social context, there are still significant differences in understanding the concept and application of Pancasila. This article examines the realities and challenges of realizing Pancasila as the nation's moral and intellectual foundation. Examining the context current social, political and cultural aspects, this article highlights efforts to understand the values ​​of Pancasila in depth and apply them in everyday life.